Beautification and efficiency improvement of 3D modelling with the help of geometric constraints. (2016) - Annich, Afafe; Abderrahmani, Abdellatif El; Satori, Khalid
We emphasise on the influence of geometric constraints in 3D reconstruction. In fact, we have used a new approach of 3D reconstruction which is based on bundle adjustment optimisation and constraints. Our purpose is to achieve 3D reconstruction in a simple, fast and efficient way without any prior information about cameras and 3D space. Constraints use brings us many advantages; it helps us to reduce estimated parameters number and stabilises good results quality. We try as much as possible through a comparative analysis to prove the importance of constraints use, in terms of results reliability, process speed and convergence rate. We use uncalibrated views, so we don't have any pertinent initial values used in Levenberg-Marquardt. On the hand, and thanks to the estimation of cameras' positions with constraints during Levenberg-Marquardt optimisation, we solve with the convergence problem satisfactorily. Several data will be used with the aim to demonstrate the efficiency of our present approach under different uses and kinds of constraints.